Oracle FAQ Your Portal to the Oracle Knowledge Grid
HOME | ASK QUESTION | ADD INFO | SEARCH | E-MAIL US
 

Home -> Community -> Usenet -> comp.databases.theory -> Re: armstrong's axioms: augmentation - help pls

Re: armstrong's axioms: augmentation - help pls

From: loveboat <l0veb0at_at_gmx.de>
Date: Fri, 3 Dec 2004 18:59:12 +0100
Message-ID: <coq9tm$tb$1@svr7.m-online.net>


thx guys =)

"loveboat" <l0veb0at_at_gmx.de> schrieb im Newsbeitrag news:con0pi$c5c$1_at_svr7.m-online.net...
> hi,
>
> in armstrongs axioms, i don't get the augmentation, which is:
> (X -> Y) => (XZ -> YZ)
>
> why is that? i mean when Y is functional depending from X, i can't just
add
> another set of attributes and make them dependent as well? (at least
that's
> what i think)
> why can i do that?
> thx for help,
> toni
>
>
Received on Fri Dec 03 2004 - 11:59:12 CST

Original text of this message

HOME | ASK QUESTION | ADD INFO | SEARCH | E-MAIL US